Antibiotics in the treatment of scrub typhus: A network meta-analysis and cost-effectiveness analysis - Chen, Chaoxin; Chen, Tingting; Xue, Dan; Liu, Maobai; Zheng, Bin (The Journal of Infection in Developing Countries, 2025)
Introduction: A pharmacoeconomic analysis model was developed to evaluate the cost-effectiveness of antibiotics from a societal perspective in Korea and China. A network meta-analysis was conducted to evaluate the efficacy of antibiotics. Methodology: We conducted a systematic search for randomized controlled trials or quasi-randomized controlled trials on antibiotics employed as therapy in scrub typhus management. We performed a network meta-analysis to obtain their relative efficacy. The outcome measures for efficacy were cure rate and non-relapse rate. To evaluate their relative cost-effectiveness in Korea and China, a decision analytic model simulating a cohort of scrub typhus patients using antibiotics as therapy was constructed from a societal perspective over 8 weeks. The number of cure cases per 1000 patients and the incremental cost-effectiveness ratio (ICER) was calculated. Results: We identified 11 relevant articles for network meta-analysis. Of the seven comparisons (azithromycin, chloramphenicol, doxycycline, high-dose rifampin, low-dose rifampin, telithromycin, tetracycline) included in the network meta-analysis, tetracycline was the most effective drug for the treatment of scrub typhus, but the difference is not significant. In the cost-effectiveness analysis, all the treatments were dominated by tetracycline in Korea and China. Conclusions: Tetracycline is the most economic drug for the treatment of scrub typhus. Hence, tetracycline is recommended as the first choice for the treatment of scrub typhus without contraindications in China and Korea.